Pengaruh Brand Image Terhadap Brand Loyalty Iphone Pada Mahasiswa - Ana Latifa Sri Rahayu; Lala Septiyani Sembiring; Rozi Sastra Purna (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Generation Z students are a digital generation. They have been accustomed to using smartphones from an early age until their academic life at university. The iPhone, as a smartphone brand with superior features, is one of the smartphone choices widely used by students to support academic activities on campus. The image of the iPhone is a fairly important aspect to consider in their purchasing decision-making process. In line with this, many students who have used the iPhone are reluctant to switch to using another brand, so it is interesting to investigate the influence of the iPhone's brand image on student loyalty as users. This study aims to determine the effect of brand image on brand loyalty in student iPhone smartphone users. The research method used is a quantitative research method. This study was conducted on 388 students in the city of Padang using voluntary sampling in selecting participants. Brand image was measured using an adaptation of the scale developed by Cho et al. (2015), while brand loyalty was measured using the scale from Harris and Goode (2004). In this study, a simple linear regression method was used for statistical analysis. The results of the study showed a significant influence of brand image on iPhone brand loyalty (p<.05), with a large influence of 27.5%.